THE EFFECTIVENESS OF FRAUD TRIANGLE ON DETECTING FRAUDULENT FINANCIAL STATEMENT: USING BENEISH MODEL AND THE CASE OF SPECIAL COMPANIES - Aprillia, Aprillia; Cicilia, Orlin; Pertiwi Sergius, Rafaela (Jurnal Riset Akuntansi dan Keuangan, 2015)
Fraudulent financial statement is a serious problem and to be a threat to stakeholders, especially for investor. The thing is happened because there is illegal action done intentionally, such as disclosing financial information that doesn’t match with the real condition. The purpose of this research is to acquire a effectiveness of empirical proof of fraud triangle consisting of Pressure, Opportunity, and Rationalization in detecting financial statement fraud that are indicated by using Beneish Model. The sample of this research consists of 39 companies are indicated doing fraud and 57 companies aren’t indicated doing fraud listing at BEI (Bursa Efek Indonesia) in 2012 – 2014. Test of this research uses logistic regression method. Based on the result and conclusion, this research shows that opportunity (independent commissioner ownership) has significant effect to fraudulent financial statement while pressure (AGROW), financial target (ROA), and rationalization (Total accrual) don’t have significant effect to fraudulent financial statement.